Fluoxetine regulates the neuronal differentiation of neural stem cells transplanted into rat brains after stroke by increasing the 5HT level. (16th February 2022) - Wei, Naili; Li, Ce; Zhu, Yulian; Zheng, Peiqi; Hu, Ruiping; Chen, Jian
Highlights: Fluoxetine indirectly regulates neural stem cell differentiation. 5-HT upregulats neurogenin1 expression by inhibiting ERK2 phosphorylation. Fluoxetine has the different pathways of activation. Abstract: Fluoxetine, a 5-HT uptake inhibitor, has been adopted for the treatment of post-stroke depression in recent years. It has been confirmed to induce neuronal regeneration in vivo, but its effect on inducing stem cell differentiation after transplantation has not yet been verified. To evaluate its regulatory effect on stem cell differentiation, fluoxetine was used in this study to treat rats with cerebral ischemia after neural stem cell (NSC) transplantation. The results showed that the proportion of NSCs differentiating into neurons significantly increased after fluoxetine treatment. In NSC adherent culture, the addition of 5-HT but not of fluoxetine significantly increased the neuronal differentiation ratio of NSCs. Moreover, the addition of 5-HT2A or 5-HT3A antagonists inhibited this effect. In addition, Western blotting revealed that the increase in 5-HT inhibited ERK2 phosphorylation and upregulated neurogenin1 expression. In conclusion, fluoxetine increased the 5-HT level and promoted neuronal differentiation, thereby upregulating neurogenin1 expression and downregulating ERK2 phosphorylation.